EFEKTIVITAS FORUM DISKUSI PADA E-LEARNING BERBASIS MOODLE UNTUK MENINGKATKAN PARTISIPASI BELAJAR - Soraya Fatmawati (Universitas Muria Kudus, 2019)
The study aims to find out the effectiveness of the discussion forum on Moodle based elearning to improve students learning participation. The study employs pre-experiment method with one group pretest-posttest design and analysis method uses non-parametric statistics with T-test. The study is conducted at Information Technology Department of Faculty of Education at University of Technology Yogyakarta. The research sample is taken from the fourth semester student of Information Technology Education Department who enroll theory course. Instrument used in this study is guided observation to observe students learning participation with 2 answer alternatives. The study result shows that discussion forum on Moodle based e-learning can improve students learning participation compared to discussion occurred in the conventional classroom or classical discussion with the significant result of improvement for about 37%.